Clinical and serological outcomes in patients treated with oral doxycycline for early neurosyphilis. (30th March 2021) - Girometti, Nicolò; Junejo, Muhammad H; Nugent, Diarmuid; McOwan, Alan; Whitlock, Gary; ,
Abstract: Objectives: Penicillin-based antibiotic treatment for syphilis infection with CNS involvement (early neurosyphilis) is not always a suitable treatment option. We compared outcomes of patients diagnosed with early neurosyphilis and treated with doxycycline or procaine G penicillin. Methods: Serological and clinical outcomes were analysed in patients diagnosed with early neurosyphilis between January 2015 and October 2019 at 56 Dean Street, a combined sexual health and HIV service based in London, UK. Acute onset of CNS, ocular and/or otic symptomatology and a documented seroconverting syphilis serology or a >4-fold increase in rapid plasma reagin ('RPR)' test titre within the previous 12 months were criteria used to define a case. Mann–Whitney U -test and χ 2 tests were used to test distributions between baseline characteristics and outcomes according to treatment administered. Results: Eighty-seven patients were included: median age = 35 years (IQR = 31–45), 98% MSM, 79% white ethnicity, 53% HIV-1 positive and 40% previously diagnosed with syphilis at any stage. They were treated exclusively with either intramuscular (IM) procaine G penicillin (71%) or oral doxycycline (18%). Patients received doxycycline treatment over a penicillin-based regimen due to IM treatment declined (31%), inability to attend for IM injections (31%) or penicillin allergy (19%). Serological response was achieved by all patients; 91% reported full symptom resolution at 30 days from end of treatment. Similar rates of clinical and serological response and seroreversion were observed in the groups treated with procaine G penicillin versus doxycycline. Conclusions: The clinical and serological outcomes seen with penicillin-based versus doxycycline treatments were similar. A randomized controlled trial is needed to establish the effectiveness of doxycycline in the treatment of early neurosyphilis.